In vitro characterization of polyvinyl alcohol assisted hydroxyapatite derived by sol-gel method - Kaygili, Omer; Keser, Serhat; Al Orainy, R. H.; Ates, Tankut; Yakuphanoğlu, Fahrettin (Elsevier Science Bv, 2014)
The synthesis and characterization of sol-gel derived hydroxyapatite (HAp) were investigated with the effects of the addition of polyvinyl alcohol (PVA) to the structural and material in vitro behavior. All samples were soaked in simulated body fluid (SBF) for 14 and 28 days. The characterization of bioceramics before and after immersing in SBF was carried out by X-ray diffraction (XRD). Fourier transform infrared (FTIR) spectroscopy, differential thermal analysis (DTA), thermogravimetric analysis (TGA) and scanning electron microscopy (SEM) techniques. After the simulated body fluid period, the crystal structure and phase of HAp samples did not change significantly. The characteristic bands of hydroxyl, phosphate and carbonate groups were detected. HAp exhibited a thermal stability of room temperature to 1000 degrees C. The surface morphologies of the samples show an evident change with the soaking period in SBF. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: In vitro; Hydroxyapatite; Polyvinyl alcohol; Sol-gel method